PENENTUAN URUTAN KOMPONEN UNTUK PROSES PERAKITAN PISTON - Nelce D. Muskita; Surianto Buyung; Yolanda J. Lewerissa (SOSCIED, 2026)
The objective of Design for Assembly is to optimize the assembly process by minimizing or reducing the time required for assembly. Materials used in each component, as well as the sequence in which the parts are handled and inserted, have a significant impact at formation the angles of α (alpha) and β (beta). These angles serve as reference points for determining the allotment assembly time for a component. Calculation process begins by determining the number of pieces (N) and variety of component (n) at the product to be assembled. The factors that significantly influence the arrangement of components during handling, insertion, and fastening processes are determined. Handling complexity factor is the factors affecting the handling process (Ch), while insertion complexity factor is the factors influencing the insertion process (Ci). Product Complexity Index (CIproduct) and the assembly process complexity (Cassembly process) from the product to be assembled can be calculated, where lower values indicating easier assembly and shorter assembly time, recommendations and suggestions to relevant parties.